Experimental and simulation studies on radiative properties of uranium planar target coated with an ultrathin aluminum layer. (22nd December 2017) - Guo, Liang; Yi, Taimin; Ren, Guoli; Zhang, Wenhai; Li, Sanwei; Li, Zhichao; Kuang, Longyu; Xie, Xufei; Jiang, Xiaohua; Du, Huabin; Hou, Lifei; Zhan, Xiayu; et al.
Abstract: An ultrathin aluminum (Al) layer is proposed to be coated on the surface of the uranium (U) planar target for preventing the oxidization of U and optimizing the hard x-ray spectrum. Comparative experiments using several planar targets with different materials are implemented on the Shenguang-III prototype laser facility to study their radiative properties. Under the laser intensity of 1.0 × 10 15 W cm −2, we observe that the U target coated with 30 nm thick Al produces almost the same peak intensity of the total x-ray flux and decreases the hard x-ray fraction by 38.5% compared to the U target coated with 100 nm thick gold. Simulations using XRL2D (2D radiation hydrodynamic code) interpret the measured results and indicate that the radiative property of Al-coated U approaches that of pure U, which theoretically has a high laser to x-ray conversion efficiency and a quasi-Planckian spectrum. Based on our analysis, Al-coated U is a promising material of the ignition hohlraum and should have many applications in high energy density physics.